Children's Residential Proximity, Spousal Presence and Dementia Risk - Zhuoer Lin; Xuecheng Yin; Becca R. Levy; Yue Yuan; Xi Chen (Global Labor Organization (GLO), 2024)
Cognitive impairment poses considerable challenges among older adults, with the protective role of family support becoming increasingly crucial. This study examines the role of children's residential proximity and spousal presence with dementia risk in cognitively impaired older adults. We analyzed 14,600 individuals aged 50 and older with cognitive impairment from the Health and Retirement Study (1995-2018). Family support was categorized by spousal presence and children's residential proximity. Modifiable risk factors, including smoking, depressive symptoms, and social isolation, were assessed. Mixed-effects models were estimated. A significant proportion of older adults with cognitive impairment lacked access to family support, with either no spouse (46.9%) or all children living over 10 miles away (25.3%). Those with less available family support, characterized by distant-residing children and the absence of a spouse, had a significantly higher percentage of smoking, depressive symptoms, and social isolation. Moreover, we revealed a consistent gradient in the percentage of the risk factors by the degree of family support. Relative to older adults with a spouse and co-resident children, those without a spouse and with all children residing further than 10 miles displayed the highest percentage of the risk factors. These findings were robust to various sensitivity analyses.
Keywords: I12; J14; I18; I11; 330; dementia; depression; social isolation; smoking; long-term care; family support; residential proximity